State-Induced Migration and the Creation of State Spaces in Early Chinese Empires: Perspectives from History and Archaeology. Issue 2 (July 2021) - Korolkov, Maxim; Hein, Anke
Abstract: In ancient China, as elsewhere, states did not simply occupy a given territory but actively engaged in the production of space by transforming landscapes, moving populations, and enacting territorial hierarchies, thus creating "state spaces, " to borrow a term coined by James C. Scott. In the case of the early Chinese empires of Qin (221–207 BCE) and Han (202 BCE–220 CE), state-induced migration and settlement were key instruments of military control, administrative incorporation, economic intensification, and other processes connected with spatial distribution of state power. This article combines insights from transmitted texts, excavated documents, and archaeological evidence to explore factors and effects of migration in early Chinese empires, discussing the interconnection between state-organized resettlement and private migration as well as their embeddedness in the local geography. As the situation varies according to location, the present article introduces the approach and tests it on a case study, the Guanzhong metropolitan region.